2020
DOI: 10.1016/j.heliyon.2020.e05225
|View full text |Cite|
|
Sign up to set email alerts
|

Combating homophobia, lesbophobia, biphobia and transphobia: A liberating and subversive educational alternative for desires

Abstract: The repression of human sexuality began anew in the twentieth century with a strengthening of patriarchal conceptions that pathologised sexual preferences, such as homosexuality, lesbianism and bisexuality, and medicalised transsexuality. Our educational approaches based on action research have reduced violence and empowered teenagers – girls and boys – and groups of teachers in different countries of the European Union. The diversification of assessment tools has resulted in an improved evaluation of processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…It is essential for students to be aware of the disability, understand the limitations and capacities of their classmates, as well as the way to relate or interact with them [16]. Furthermore, as stated by [9,15,17,31], despite the fact that students have contact with classmates with disabilities, this interaction does not imply that they know the correct way to relate and that mere contact generates positive attitudes. Attitudes, as indicated by [19] determine the reality of the inclusion of students with disabilities and depend on the quality of interactions and relationships.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential for students to be aware of the disability, understand the limitations and capacities of their classmates, as well as the way to relate or interact with them [16]. Furthermore, as stated by [9,15,17,31], despite the fact that students have contact with classmates with disabilities, this interaction does not imply that they know the correct way to relate and that mere contact generates positive attitudes. Attitudes, as indicated by [19] determine the reality of the inclusion of students with disabilities and depend on the quality of interactions and relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Education for all must be promoted [9], and that in this sense we must reject the attitudes of exclusion, discrimination, or rejection that still exist today in most schools. In this sense, the prioritization of positive relationships and effective coexistence among all students stands out.…”
Section: Diversity As a Valuementioning
confidence: 99%
“…The situation is further exacerbated in undeveloped regions where students have fewer educational resources [19]. Last, although a study in Europe has reported reduced violence and greater respect for sexual diversity through educational intervention [20], such issues have been rarely introduced in the current sexuality education curriculum in China.…”
Section: Introductionmentioning
confidence: 99%
“…Hostility: Homophobia or transphobia are hostile attitudes towards individuals belonging to the LGBTQIA+ collective, including hatred, the singling out of the LGBTQIA+ individual as contrary, inferior or abnormal and, in the case of psychiatric discourse, placing it in the pathological or symptomatic range [55,57].…”
mentioning
confidence: 99%
“…• Domestic political action: As students must focus on presenting the proposals and issues of the LGBTQIA+ network to ordinary people working in all trades by lobbying the university in order to include the issue of sexual diversity in their agendas, in an attempt to naturalize and institutionalize the issue of homosexuality, bisexuality and transsexuality, making it a matter of social and public interest [30,37,57].…”
mentioning
confidence: 99%